Students’ preferences for mobile phone service providers based on fuzzy grade matrix and statistical analysis - Osman, Roselah; Ramli, Nazirah; Ujang, Suriyati (GADING Journal for the Social Sciences, 2024)
Selecting the most appropriate mobile phone network service provider can be challenging due to factors such as limited network coverage, varied service offerings, and other influencing factors. This study aims to identify the factors influencing university students' preferences for mobile phone network service providers in Malaysia. To address the vagueness and imprecision inherent in human evaluation, a fuzzy grade matrix was developed to analyse the ratings of performance based on sub-criteria. The methodology comprises two main parts: fuzzy grade matrix analysis and statistical analysis. The fuzzy grade matrix process includes calculating the fuzzy weight and grades based on the importance and performance levels of each criterion, constructing the fuzzy grade matrix, determining the ranking of alternatives, and interpreting the results. In parallel, the statistical analysis uses Spearman’s rank correlation to measure the strength and direction of relationships between the influencing factors and students' choices. This analysis identified price, service quality, and coverage as the most significant factors influencing students' decisions. Based on the fuzzy grade matrix, Unifi was identified as the most preferred mobile network service provider by students, while U Mobile was the least preferred. However, the analysis also revealed that students rated all service providers relatively low overall, despite Unifi's top ranking. This study highlights the need for mobile network service providers to consider additional important criteria that influence students’ decision-making processes to better cater to their preferences.